Antioxidant, thrombolytic, cytotoxic and antibacterial activities of leaves of Vitex peduncularis - Islam, MS; Al Mansur, MA; Rakhi, SA; Sarkar, MR; Kuddus, MR; Ahmed, Firoj (Bangladesh Journal of Scientific and Industrial Research, 2022)
Vitex peduncularis (Verbenaceae), a perennial tree, is locally utilized for possessing multifaceted pharmacological properties including analgesic, antimalarial, anti-angina, antidiabetic, antioxidant, anti-inflammatory and hepatoprotective. Hence, this study aims to evaluate their antioxidant, thrombolytic, cytotoxic and antibacterial activities from the methanolic crude extract and its various solvent fractions. Data from antioxidant and thrombolytic assay displayed that Kupchan partitioned chloroform soluble fraction revealed the maximum phenolic content (73.39 mg of GAE/g of extract), DPPH free radical scavenging activity (26.69 μg/ml) and thrombolytic activity (37.35%). In brine shrimp lethality evaluation, the LC50 values indicate that the most cytotoxic compound was found to be from ethyl acetate soluble fraction (LC50 6.73 μg/ml). Finally, antibacterial activity of different fractions showed that both chloroform and methanolic fraction possessed mild activity against the tested bacteria. The potential biological effects of the crude fractions have been demonstrated demanding future studies of the isolated compounds to assess these activities. Bangladesh J. Sci. Ind. Res. 57(4), 239-246, 2022